PEGylation may reduce allergenicity and improve gelling properties of protein isolate from black kidney bean (Phaseolus vulgaris L.). (October 2018) - Yang, Yufei; He, Qian; Sun, Hanju; Cao, Xiaodong; Elfalleh, Walid; Wu, Zeyu; Zhao, Jinlong; Sun, Xianbao; Zhang, Yang; He, Shudong
Abstract: Effects of PEGylation with methoxy polyethylene glycol (mPEG) on gelling properties of black kidney bean protein isolate (BKBPI) were investigated. PEG-protein conjugations were confirmed using SDS-PAGE, and a significant decrease of allergenicity was observed using an ELISA test. Gelling concentration and gelling properties of BKBPI and mPEG-BKBPI with various treatments, including the additions of NaCl and N-ethylmaleimide (NEM) as well as a heat pretreatment were evaluated. Results showed that the critical gelling concentration of PEGylated BKBPI was 75 mg/ml, and the PEGylation resulted in a higher gelling strength and a shorter gelling time compared with the native BKBPI. The increases in gel strengths were observed both in BKBPI and mPEG-BKBPI with the addition of NaCl, and no obvious variations in storage modulus (G') were found after PEGylation even at a high NaCl concentration of 1 mol/l. Meanwhile, retardation of the G' was observed in the PEGylated protein with the addition of NEM. Furthermore, the G' increased significantly after preheating. Therefore, the results suggested that PEGylation was beneficial to the safety and gelling properties of BKBPI and served to extend applications of BKBPI. Graphical abstract: Highlights: Black kidney bean protein isolates (BKBPI) were modified using mPEG derivatives. Allergenicity and gelling concentration of PEGylated BKBPI were reduced. Higher gelling strength and shorter gelling time were obtained using PEGylation. Gel properties were improved with the NaCl, NEM and preheating treatments.